Is Growth Enough? : Macroeconomic Policy and Poverty Reduction - Leite, Carlos (IMF Working Papers; Working Paper, 2002)
The paper investigates the existence of "super pro-poor" policies-that is, policies that directly influence the income of the poor after accounting for the effect of growth. It uses a dynamic panel estimator to capture both across- and within-country effects, and a Bayesian-type robustness check to account for model uncertainty. The findings confirm that growth raises the income of the poor, although this relationship is less than one-to-one. The analysis also identifies four super pro-poor conditions that are influenced by policy: inflation, government size, educational achievement, and financial development.